2023
DOI: 10.1002/adfm.202211740
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State Homojunction Electrochemical Transistors and Logic Gates on Plastic

Abstract: Organic electrochemical transistors (OECTs) have attracted significant attention due to their unique ionic-electronic charge coupling, which holds promise for use in a variety of bioelectronics. However, the typical electronic components of OECTs, such as the rigid metal electrodes and aqueous electrolytes, have limited their application in solid-state bioelectronics that requires design flexibility and a variety of form factors. Here, the fabrication of a solid-state homojunction OECT consisting of a pristine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…When V DD = 1.2 V, the inverter demonstrates the highest gain of 11.48 (Figure 2K), which is comparable to or higher than the performance of IGTbased inverters reported in the literature. [32,51,52] The aforementioned results indicate that the modified all-photolithography method can be used for the construction of complex logic circuits.…”
Section: The Uniformity Of An Oigt Arraymentioning
confidence: 93%
“…When V DD = 1.2 V, the inverter demonstrates the highest gain of 11.48 (Figure 2K), which is comparable to or higher than the performance of IGTbased inverters reported in the literature. [32,51,52] The aforementioned results indicate that the modified all-photolithography method can be used for the construction of complex logic circuits.…”
Section: The Uniformity Of An Oigt Arraymentioning
confidence: 93%
“…Thus, the development of foundry-compatible organic semiconductors patterning methods that maintains device performance has potentially revolutionize the OECT industry [142,143]. Recently, Kwak et al reported photo-patternable organic mixed ionic and electronic conductors (OMIECs) by introducing a photocross-linkable material (thane-1,2-diyl bis(4-azido-2,3,5,6 tetrafluorobenzoate)) into ion-conducting conjugated polymers to address these challenges (figure 4(b)).…”
Section: Photolithographymentioning
confidence: 99%
“…This chemistry of the cross-linking reactions involving azido compounds relies on the highly efficient and selective click chemistry reactions, enabling the formation of stable and robust crosslinkages in polymer networks. The patterning technique is exceptionally efficient as it only necessitates three steps, making the manufacture process simpler than conventional photolithography [142], in which a blend film of semiconductor/electrolyte and crosslinkers can be patterned directly via UV light-triggered crosslinking. With this patterning technology, flexible OECTs were evaluated and presented high carrier mobility (3.4 cm 2 V −1 s −1 ) and reliabe mechanical stability, with minimal degradation in OECT output performance, even after undergoing 5000 bending cycles at radius of only 0.1 mm.…”
Section: Photolithographymentioning
confidence: 99%
“…Molecular doping strategies have been applied to OMIECs, both for p-and n-type materials, which have been successful in modulating current densities, shifting threshold voltages, minimizing side reactions, and improving long-term stability in OECTs. [74][75][76] Other small molecule additives have been employed to improve the output characteristics of OECTs. 77 Moreover, the de-doping of PEDOT:PSS has been achieved by promoting interactions between amine groups and PSS-, allowing the generate a polymer for use in enhancement mode OECTs.…”
Section: Post-processing and Additivesmentioning
confidence: 99%